Metal-intermetallic compound composite material with brick-mud structure and preparation method of metal-intermetallic compound composite material
Through multi-thin foil stacking and two-stage sintering methods, metal-intermetallic compound composite materials of brick mud structures are prepared, which solves the problem of early failure of the layered structure, improves the comprehensive mechanical properties of the material, and is suitable for a variety of applications.
Patent Information
- Application Number
- CN202510597002.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-09
- Publication Date
- 2025-08-15
AI Technical Summary
Layered structure metal-intermetallic compound composites are prone to interlayer cracks during loading, resulting in early failure, limiting the material's load-bearing capacity.
Using multi-thin foil stacking and two-stage preparation method, the continuously distributed intermetallic compounds are converted into discontinuous sheet-like intermetallic compounds through vacuum hot pressing and sintering technology to form a brick mud structure to enhance the strength and toughness of the material.
It significantly improves the strength and toughness of the composite material, weakens the influence of anisotropy, and is closer to shell structure in bionics, and is suitable for a variety of applications.
Smart Images

Figure CN120481427A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of bionic composite materials, and relates to a composite material with a brick-mud structure and a preparation method thereof, and in particular to a metal-intermetallic compound composite material with a brick-mud structure and a preparation method thereof. Background Art
[0002] As scientists explore the nature in depth, they find that natural biomaterials exhibit excellent mechanical properties due to their unique biological structure. The shell nacre has a unique laminated structure, which makes the shell's strength and toughness perfectly balanced, and its overall performance is far superior to that of a single component. Studies have found that this laminated structure has a special energy dissipation mechanism, which provides a feasible structural design idea for the design of artificial materials with unique properties. Inspired by this, researchers have conducted research on bionic layered composites, aiming to develop high-performance protective materials for equipment. Since the 1990s, the design and development of metal-intermetallic laminated (MIL) composites have achieved remarkable results. At present, MIL composite materials of various systems have been successfully prepared, including Ti-Al system, Ni-Al system, Fe-Al system, Ni-Ti system, etc.
[0003] Methods for preparing layered composite materials primarily include explosive welding, rolling cladding (cold rolling and hot rolling), (non-)vacuum hot pressing sintering, pulsed current thermal processing, and ultrasonic consolidation. Hot pressing sintering, due to its flexibility in varying the stacking order of raw materials, layer thickness, and precise control of reaction conditions, has become a reasonable choice for preparing metal-intermetallic compound layered composites.
[0004] Traditional metal-intermetallic compound layered composites can effectively improve the strength and toughness of traditional single metals. Their unique layered structure can absorb a large amount of energy during crack deflection and delamination. However, simply adjusting simple parameters such as the layer thickness ratio has limited effect on significantly improving the mechanical properties of layered composites. In order to improve the performance of layered composites, researchers have used different methods to improve the comprehensive performance of layered composites, including introducing fiber-reinforced composites between layers and modifying intermetallic compounds through alloying.
[0005] The presence of brittle intermetallic compounds in layered composite materials often leads to rapid expansion of cracks along the interlayer interface, causing early fracture, which greatly limits the material's bearing capacity. However, the polygonal sheet structure (brick-mud structure) of brittle aragonite in the shell nacre does not show a similar phenomenon. The present invention addresses the problem of early failure caused by interlayer cracks in layered structures during loading. Ti foil and Al foil are used as raw materials, and a "multi-thin foil" stacking and "two-stage" preparation method are adopted to prepare a metal-intermetallic compound composite material with a microscale brick-mud structure. The continuously distributed intermetallic compound is successfully converted into a discontinuously distributed sheet-like intermetallic compound, effectively improving the strength and toughness of the composite material. Summary of the Invention
[0006] The purpose of the present invention is to solve the problem that layered structures are prone to interlayer cracking and cause early failure of materials, and to provide a method for structurally modifying metal-metal intermetallic compound layered composite materials. The brick-mud structure composite material can greatly improve the strength and toughness of the layered composite material.
[0007] The present invention provides a method for preparing a metal-intermetallic compound composite material with a brick-mud structure, comprising the following steps:
[0008] Step 1: Pre-treat the metal foil and Al foil; stack the treated foils in a unit of metal foil-Al foil, so that the outermost layer of the stacked sample is all metal foil;
[0009] Step 2: The stacked samples are placed in a vacuum hot press furnace for pre-sintering to obtain a metal-intermetallic compound layered composite material;
[0010] Step 3: placing the metal-intermetallic compound layered composite material in a vacuum hot pressing furnace for secondary sintering, and finally obtaining a metal-intermetallic compound composite material with a brick-mud structure.
[0011] Furthermore, in step 1, the pretreatment is to polish the surface of the metal foil and the Al foil with metallographic sandpaper, and then place them in an ultrasonic cleaner for cleaning after polishing, and the washing time is 15 to 20 minutes; after washing, the metal foil and the Al foil are washed and dried with alcohol.
[0012] Furthermore, in step 1, the metal foil is selected to be able to form a stable Al-rich intermetallic compound with Al foil under high temperature and high pressure conditions; the thickness of the Al foil is 0.01 to 2 mm; the thickness of the metal foil is 0.01 to 2 mm.
[0013] Furthermore, the metal foil is preferably one of titanium, titanium alloy, nickel, nickel alloy, iron, and iron alloy.
[0014] Furthermore, in step 1, the number of the stacking units is 30 to 100, including n metal layers and n-1 Al layers, where n is 31 to 101; the metal layers and Al layers are arranged alternately in a periodic manner, and the upper and lower outermost layers are both metal foils.
[0015] Furthermore, in step 2, the pre-sintering operation is as follows: first, at a pressure of 2 to 5 MPa, the temperature is increased to 500 to 600°C at a rate of 5 to 10°C / min and kept warm for 10 to 30 minutes; then the pressure is reduced to 0.1 to 2 MPa, the temperature is increased to 655 to 665°C at a rate of 2 to 5°C / min and kept warm for 60 to 240 minutes; finally, the pressure is increased to 10 to 15 MPa, the temperature is increased to 700 to 1000°C at a rate of 5 to 10°C / min and kept warm for 10 to 30 minutes to extrude the remaining Al; after pre-sintering, the pressure is maintained at 1 to 2 MPa and the furnace is cooled to room temperature.
[0016] Furthermore, in step 3, first, under a pressure of 2 to 5 MPa, the temperature is raised to 600 to 660°C at a rate of 5 to 10°C / min and kept warm for 10 minutes; then the pressure is increased to 20 to 30 MPa, the temperature is raised to 800 to 1000°C at a rate of 5 to 10°C / min and kept warm for 5 to 60 minutes; after the secondary sintering, the pressure is maintained at 1 to 2 MPa and the furnace is cooled to room temperature.
[0017] The present invention also provides a metal-intermetallic compound composite material with a brick-mud structure.
[0018] Furthermore, in the composite material, the metal-Al intermetallic compound acts as a matrix "brick" and the metal acts as "mud".
[0019] Furthermore, when the loading direction is perpendicular to the layer direction, the ultimate compressive strength of the composite material is 1500-1800 MPa; when the loading direction is parallel to the layer direction, the ultimate compressive strength of the composite material is 1400-1600 MPa.
[0020] The beneficial effects of the present invention are:
[0021] (1) The present invention optimizes the layered structure into a brick-and-mud structure, which is closer to the shell structure in bionic research.
[0022] (2) The present invention can conveniently design the type and structure of the composite material by changing the type of starting foil, foil thickness and reaction conditions, and can prepare a variety of metal-intermetallic compound composite materials with multi-scale brick-mud structures to meet the requirements of different application scenarios.
[0023] (3) The metal-intermetallic compound composite material with a brick-mud structure prepared by the present invention is prepared by a secondary hot pressing and sintering method, and exhibits better strength and toughness than the metal-intermetallic compound with a layered structure, while greatly reducing the influence of anisotropy. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 is a process flow chart of the present invention;
[0025] Figure 2 This is a SEM image of the microstructure of the pre-sintered sample in Example 1;
[0026] Figure 3 This is a SEM image of the microstructure of the brick-mud structure sample in Example 1;
[0027] Figure 4 This is a three-dimensional reconstruction of the brick-and-mud structure sample in Example 1;
[0028] Figure 5 is a quasi-static compressive stress-strain curve of the sample in Example 1;
[0029] Figure 6 This is the microstructure SEM image of the brick-mud structure sample in Example 2;
[0030] Figure 7 This is the SEM image of the microstructure of the brick-mud structure sample in comparative example 1. DETAILED DESCRIPTION
[0031] The present invention will be further described below with reference to the accompanying drawings.
[0032] The present invention discloses a method for preparing a metal-intermetallic compound composite material of a brick-mud structure, such as Figure 1 Shown, including:
[0033] Cut 0.01-2mm Al foil and 0.01-2mm Ti foil into squares. Chemically polish the Ti and Al foil surfaces with metallographic sandpaper to remove the oxide layer. Then, clean the foil in an ultrasonic cleaner for 15-20 minutes to remove any remaining oxide particles and impurities. Finally, clean and dry the foil with alcohol. Stack the foils in "metal foil-Al foil" units, with 30-100 units stacked, with both the upper and lower outer layers made of metal foil.
[0034] The stacked samples are placed in a vacuum hot pressing furnace for pre-sintering, and the preparation process is as follows: The laid-out laminated samples are placed in a vacuum hot pressing furnace for pre-sintering, and the preparation process is as follows: the first step is to increase the temperature to 500-600°C at a rate of 5-10°C / min and keep warm for 10-30 minutes, and the pressure is 2-5MPa; the second step is to increase the temperature to 655-665°C at a rate of 2-5°C / min and keep warm for 60-240 minutes, and the pressure is 0.1-2MPa; the third step is to increase the temperature to 700-1000°C at a rate of 5-10°C / min and keep warm for 10-30 minutes, and the pressure is 10-15MPa to extrude the remaining Al; the fourth step is to cool to room temperature with the furnace, and the pressure is maintained at 1-2MPa.
[0035] The metal-intermetallic compound layered composite material obtained by pre-sintering is cut into circular specimens with a diameter of 1.5 to 2.5 cm and placed in a grinding tool with a diameter of 3 to 5 cm for secondary sintering. The preparation process is as follows: first, heating to 600 to 660°C at a rate of 5 to 10°C / min and holding at this temperature for 10 minutes at a pressure of 2 to 5 MPa; second, heating to 800 to 1000°C at a rate of 5 to 10°C / min and holding at this temperature for 5 to 60 minutes at a pressure of 20 to 30 MPa; third, cooling to room temperature in the furnace while maintaining the pressure at 1 to 2 MPa. The final result is a brick-mud structure metal-intermetallic compound composite material.
[0036] Example 1
[0037] A method for preparing a metal-intermetallic compound composite material with a brick-mud structure comprises the following steps:
[0038] Step 1: Cut 0.1mm Al foil and 0.1mm Ti foil into 7×7cm squares. Polish the Ti and Al foil surfaces with metallographic sandpaper to remove the oxide layer. Then, clean the foil in an ultrasonic cleaner for 15-20 minutes to remove any remaining oxide particles and impurities. Finally, clean and dry the foil with alcohol. Stack the foils in a "Ti foil-Al foil" unit, creating a total of 60 units, with the top and bottom outer layers each consisting of Ti foil.
[0039] Step 2: Place the stacked samples in a vacuum hot pressing furnace for sintering. The preparation process is as follows: Place the laid-out laminated samples in a vacuum hot pressing furnace for pre-sintering. The preparation process is as follows: Step 1, heat to 600°C at a rate of 10°C / min and keep warm for 30 minutes, with a pressure of 3MPa; Step 2, heat to 660°C at a rate of 5°C / min and keep warm for 120 minutes, with a pressure of 1MPa; Step 3, heat to 700°C at a rate of 10°C / min and keep warm for 30 minutes, with a pressure of 10MPa; Step 4, cool to room temperature with the furnace, and maintain the pressure at 2MPa.
[0040] Step 3: The layered Ti-Al3Ti composite material obtained by pre-sintering was cut into circular specimens with a diameter of 2 cm and placed in a grinding tool with a diameter of 3 cm for secondary sintering. The preparation process was as follows: Step 1, heating to 660°C at a rate of 10°C / min and keeping warm for 10 minutes, with a pressure of 3.5 MPa; Step 2, heating to 900°C at a rate of 10°C / min and keeping warm for 30 minutes, with a pressure of 20 MPa; Step 3, cooling to room temperature with the furnace, and maintaining the pressure at 2 MPa.
[0041] The SEM photos of the pre-sintered samples obtained in this embodiment are shown in the attached Figure 2 It can be seen that the pre-sintered sample shows a layered structure, in which Ti layers and Al3Ti layers are arranged alternately, and there is no obvious middle line or defect after sintering.
[0042] The SEM micrographs of the secondary sintered samples obtained in this embodiment are shown in the attached Figure 3 After secondary sintering, the Al3Ti layer breaks apart, and the Ti layer fully fills the broken gaps, forming a typical "brick-and-mud" structure, with Al3Ti as the "bricks" and Ti as the "mud." Compared to the layered structure, the brick-and-mud structure is more similar to the structure of a shell from a biomimetic perspective.
[0043] The three-dimensional reconstruction of the brick-mud structure sample prepared in this embodiment is shown in the attached Figure 4 The lamellar Al3Ti phase is uniformly and orderly distributed in the Ti-Al3Ti MIL composite. The tough Ti fills the gaps between adjacent Al3Ti and acts as the overall structural framework.
[0044] The quasi-static compressive stress-strain curves of the samples prepared in this embodiment are shown in the attached Figure 5 The compressive strain rate was ~0.001 / s. When loaded perpendicular to the layer direction, the ultimate compressive strengths of the layered and masonry samples were 1140±35MPa and 1696±33MPa, respectively. Parallel to the layer direction, the ultimate compressive strengths of the layered and masonry samples were 581±25MPa and 1464±39MPa, respectively. This comparison reveals that the overall mechanical properties of the masonry samples were significantly improved.
[0045] Example 2
[0046] The raw material pretreatment in step 1 and the pre-sintering process in step 2 of this comparative example are the same as those in Example 1.
[0047] The difference from Example 1 is step 3. The secondary sintering preparation process is as follows: the first step is to heat to 660°C at a rate of 10°C / min and keep warm for 10 minutes, and the pressure is 3.5 MPa; the second step is to heat to 800°C at a rate of 10°C / min, keep warm for 30 minutes, and the pressure is 25 MPa; the third step is to cool to room temperature with the furnace, and the pressure is maintained at 2 MPa.
[0048] The SEM micrographs of the secondary sintered samples obtained in this embodiment are shown in the attached Figure 6 , it was observed that a dense "brick and mud" structure was formed under this condition.
[0049] Comparative Example 1
[0050] The raw material pretreatment in step 1 and the pre-sintering process in step 2 of this comparative example are the same as those in Example 1.
[0051] The difference from Example 1 is step 3. The secondary sintering preparation process is as follows: the first step is to heat to 660°C at a rate of 10°C / min and keep warm for 10 minutes, and the pressure is 3.5 MPa; the second step is to heat to 900°C at a rate of 10°C / min without keeping warm, and the pressure is 20 MPa; the third step is to cool to room temperature with the furnace, and the pressure is maintained at 2 MPa.
[0052] The SEM micrograph of the secondary sintered sample obtained in this comparative example is attached. Figure 7 , the secondary sintering did not form a dense "brick mud" structure. After the Al3Ti was broken, due to the lack of heat preservation operation at high temperature, the tough Ti could not fill the gaps in time, resulting in a large number of gaps.
[0053] In summary, the present invention belongs to the field of preparation of metal-intermetallic compound layered composite materials, and the object is to provide a method for preparing a metal-intermetallic compound layered composite material with a brick-mud structure. Therefore, the present invention is directed to the organizational and performance requirements of the metal-intermetallic compound layered composite material, adopts a method of pre-sintering-high temperature and high pressure secondary sintering, optimizes the process, improves the microstructure of such composite materials, and effectively improves their comprehensive mechanical properties. It is noteworthy that the present invention can adopt many types of metal foil materials, and the original X foil material (such as Ti, Fe, Ni, titanium alloy, nickel alloy, etc.) reacts with Al foil to generate Al-rich brittle metal compounds, which can be broken into bricks under hot pressing, and the tough metal X phase fills the gaps by plastic flow, and can prepare metal-intermetallic compound composite materials with different brick-mud structures to meet the requirements of different applications.
[0054] In order to achieve the purpose of the present invention, the technical solution of the present invention is described in detail through specific implementation cases. It should be understood that the implementation cases are used to illustrate the present invention rather than to limit the present invention. Simple improvements to the present invention based on the concept of the present invention fall within the scope of protection required by the present invention.
Claims
1. A method for preparing a metal-intermetallic compound composite material with a brick-mud structure, characterized in that: The following steps are involved: Step 1: Pre-treat the metal foil and Al foil; stack the treated foils in a unit of metal foil-Al foil, so that the outermost layer of the stacked sample is all metal foil; Step 2: The stacked samples are placed in a vacuum hot press furnace for pre-sintering to obtain a metal-intermetallic compound layered composite material; Step 3: placing the metal-intermetallic compound layered composite material in a vacuum hot pressing furnace for secondary sintering, and finally obtaining a metal-intermetallic compound composite material with a brick-mud structure.
2. The method for preparing the metal-intermetallic compound composite material of the brick-mud structure according to claim 1, characterized in that: In step 1, the pretreatment is to polish the surface of the metal foil and the Al foil with metallographic sandpaper, and then place them in an ultrasonic cleaner for cleaning for 15 to 20 minutes; after washing, the metal foil and the Al foil are washed and dried with alcohol.
3. The method for preparing the metal-intermetallic compound composite material of the brick-mud structure according to claim 1, characterized in that: In step 1, the metal foil is selected to be able to form a stable Al-rich intermetallic compound with Al foil under high temperature and high pressure conditions; the thickness of the Al foil is 0.01 to 2 mm; the thickness of the metal foil is 0.01 to 2 mm.
4. The method for preparing the metal-intermetallic compound composite material of the brick-mud structure according to claim 3, characterized in that: The metal foil is preferably one of titanium, titanium alloy, nickel, nickel alloy, iron, and iron alloy.
5. The method for preparing the metal-intermetallic compound composite material of the brick-mud structure according to claim 1, characterized in that: In step 1, the number of stacking units is 30 to 100, including n metal layers and n-1 Al layers, where n is 31 to 101; the metal layers and Al layers are arranged alternately in a periodic manner, and the upper and lower outermost layers are both metal foils.
6. The method for preparing the metal-intermetallic compound composite material with a brick-mud structure according to claim 1, characterized in that: In step 2, the pre-sintering operation is as follows: first, under a pressure of 2 to 5 MPa, the temperature is raised to 500 to 600°C at a rate of 5 to 10°C / min and kept warm for 10 to 30 minutes; then the pressure is reduced to 0.1 to 2 MPa, the temperature is raised to 655 to 665°C at a rate of 2 to 5°C / min and kept warm for 60 to 240 minutes; finally, the pressure is increased to 10 to 15 MPa, the temperature is raised to 700 to 1000°C at a rate of 5 to 10°C / min and kept warm for 10 to 30 minutes to extrude the remaining Al; after pre-sintering, the pressure is maintained at 1 to 2 MPa and the furnace is cooled to room temperature.
7. The method for preparing the metal-intermetallic compound composite material with a brick-mud structure according to claim 1, characterized in that: In step 3, first, under a pressure of 2 to 5 MPa, the temperature is raised to 600 to 660°C at a rate of 5 to 10°C / min and kept warm for 10 minutes; then the pressure is increased to 20 to 30 MPa, the temperature is raised to 800 to 1000°C at a rate of 5 to 10°C / min and kept warm for 5 to 60 minutes; after the secondary sintering, the pressure is maintained at 1 to 2 MPa and the furnace is cooled to room temperature.
8. A metal-intermetallic compound composite material with a brick-mud structure prepared by the preparation method according to any one of claims 1 to 7.
9. The metal-intermetallic compound composite material with a brick-and-mud structure according to claim 8, characterized in that: In the composite material, the metal-Al intermetallic compound acts as a matrix "brick" and the metal acts as "mud".
10. The metal-intermetallic compound composite material with a brick-and-mud structure according to claim 8, characterized in that: When the loading direction is perpendicular to the layer direction, the ultimate compressive strength of the composite material is 1500-1800 MPa; when the loading direction is parallel to the layer direction, the ultimate compressive strength of the composite material is 1400-1600 MPa.
Citation Information
Cited By
Fe / Al layered composite material based on continuous carbon fibers and preparation method of Fe / Al layered composite material
CN120817822A